2007
DOI: 10.1037/0003-066x.62.6.555
|View full text |Cite
|
Sign up to set email alerts
|

The Kitty Genovese murder and the social psychology of helping: The parable of the 38 witnesses.

Abstract: This article argues that an iconic event in the history of helping research -- the story of the 38 witnesses who remained inactive during the murder of Kitty Genovese -- is not supported by the available evidence. Using archive material, the authors show that there is no evidence for the presence of 38 witnesses, or that witnesses observed the murder, or that witnesses remained inactive. Drawing a distinction between the robust bystander research tradition and the story of the 38 witnesses, the authors explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 32 publications
2
140
0
2
Order By: Relevance
“…For instance, although accounts of the number of witnesses vary widely (Manning, Levine, & Collins, 2007), the rape and murder of Kitty Genovese in New York in 1964 evoked controversy and outrage, as it was reported that upwards of 38 witnesses saw or heard the crime without intervening.…”
Section: Diffusion Of Responsibilitymentioning
confidence: 99%
“…For instance, although accounts of the number of witnesses vary widely (Manning, Levine, & Collins, 2007), the rape and murder of Kitty Genovese in New York in 1964 evoked controversy and outrage, as it was reported that upwards of 38 witnesses saw or heard the crime without intervening.…”
Section: Diffusion Of Responsibilitymentioning
confidence: 99%
“…This research staged an event where helping behavior of naturally present bystanders was elicited in a situation where a person (acting in cooperation with researchers) seemed in urgent need of assistance, but not because this person was at risk of becoming a crime victim. They coined the term "bystander effect," and showed that the likelihood of a bystander intervening is a function of the number of other bystanders present (see also [29]). …”
Section: Field Testsmentioning
confidence: 99%
“…Consider, for example, how textbooks reproduce historical myths in Kuhnian fashion such as Watson and Rayner's (1920) 'Little Albert' studies (Harris, 1979) or the linear, 'official' stories surrounding 'classic' experiments in social psychology (Cherry, 1995). Manning, Levine and Collins's (2007) recent demonstration that the Kitty Genovese murder has been misrepresented for decades in undergraduate psychology textbooks shows that this process is ongoing, rather than complete. Thus, it is important to ask why, how and with what effects widely known myths about the history of psychology entrench themselves in popular accounts, rather than simply to undertake a revisionist project of 'correction'.…”
Section: Theorizing Biograp H Y Problematizing Dichotomies and Boundmentioning
confidence: 99%